Budaya Kerja Pegawai Pada Biro Umum Sekretariat Daerah Provinsi Sulawesi Utara - Mongan, Adeleida F (JURNAL ILMIAH SOCIETY, 2015)
Employees in carrying out its duties and functions not in accordance with the vision, mission, goals and objectives of the work as a reflection of the application of the basic values ​​of work culture as the State apparatus. This research was conducted with the aim of analyzing the culture of employees working at the General Secretariat of the Regional Bureau of North Sulawesi to the design used is qualitative .This study concludes that the work culture in the agency has not fully unite the way of thinking , behaving and acting employees who look at the work discipline, openness, mutual respect and cooperation. By her need to make adjustments to the work culture of the organization working with the leader become exemplary in every execution of tasks that can be manifested in attitudes and behavior on a daily basi . Keywords : Work Culture, Employees, Public Organization